Insulin-like growth factor-binding protein 5 (Igfbp5) compromises survival, growth, muscle development, and fertility in mice - Salih, Dervis A. M. (National Academy of Sciences, 2004)
The insulin-like growth factors (IGFs) are essential for development; bioavailable IGF is tightly regulated by six related IGF-binding proteins (IGFBPs). Igfbp5 is the most conserved and is developmentally up-regulated in key lineages and pathologies; in vitro studies suggest that IGFBP-5 functions independently of IGF interaction. Genetic ablation of individual Igfbps has yielded limited phenotypes because of substantial compensation by remaining family members. Therefore, to reveal Igfbp5 actions in vivo, we generated lines of transgenic mice that ubiquitously overexpressed Igfbp5 from early development. Significantly increased neonatal mortality, reduced female fertility, whole-body growth inhibition, and retarded muscle development were observed in Igfbp5-overexpressing mice. The magnitude of the response in individual transgenic lines was positively correlated with Igfbp5 expression. Circulating IGFBP-5 concentrations increased a maximum of only 4-fold, total and free IGF-I concentrations increased up to 2-fold, and IGFBP-5 was detected in high M(r) complexes; however, no detectable decrease in the proportion of free IGF-I was observed. Thus, despite only modest changes in IGF and IGFBP concentrations, the Igfbp5-overexpressing mice displayed a phenotype more extreme than that observed for other Igfbp genetic models. Although growth retardation was obvious prenatally, maximal inhibition occurred postnatally before the onset of growth hormone-dependent growth, regardless of Igfbp5 expression level, revealing a period of sensitivity to IGFBP-5 during this important stage of tissue programming.